Calcium Effect on the Soil Sedimentation – Measurement Methode - Sebők, András; Razane, Akil; Takács, Anita (Journal of Central European Green Innovation, 2022)
Nutrients such as phosphate and soil particles are much more susceptible to loss with sediments in eroding soil and run-off water, and this loss due to the erosion has a negative influence on agricultural output. To prevent it, various approaches have been taken, including the idea that particle driven coagulation may speed up sedimentation and minimize the quantity of material lost. The specific purpose of this study was to examine the efficiency of bivalent salt-based coagulants in enhancing the sedimentation process in the laboratory in a flow-through sedimentation tank. The effect of Ca2+ cations was studied by adding a 100 mg/L solution of the chemicals in a flow-through tank. A soil solution of 0.10 g/L concentration was flowing in the tank at a flow rate of 40 mL/min.  The pictures were analyzed by using ImageJ program (analyze and collect data), Origin 6.0 program (plot a graph with multi Y axis) and Surfer 12 program (make 3D model) to assess sedimentation progress. We verified that the addition of a certain amount of divalent cations, calcium, to the tank improved settling of the sediments.